Climate change multidecadal and beyond - NTU International Science Conference on Climate Change (2012 : National Taiwan University); Chang, C.-P. (Chih-Pei). (Singapore : World Scientific Publishing Co. Pte. Ltd., 2016)
'This book focuses on two major challenges in the climate sciences: 1) to describe the decadal-to-centennial variations in instrumental and proxy records; and 2) to distinguish between anthropogenic variations and natural variability. The National Taiwan University invited some of the world's leading experts across the areas of observational analysis, mathematical theory, and modeling to discuss these two issues. The outcome of the meeting is the 23 chapters in this book that review the state of the art in theoretical, observational and modeling research on internal, unforced and externally forced climate variability. The main conclusion of this research is that internal climate variability on decadal and longer time scales is so large that sidestepping it may lead to false estimates of the climate's sensitivity to anthropogenic forcing.'--
Title from PDF file title page (viewed September 21 2015).
Includes bibliographical references.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Climatic changes -- Congresses; Global warming -- Congresses; Electronic books